2009
DOI: 10.1017/s1092852900020307
|View full text |Cite
|
Sign up to set email alerts
|

Extended Release Quetiapine Fumarate Monotherapy for Major Depressive Disorder: Results of a Double-Blind, Randomized, Placebo-Controlled Study

Abstract: Introduction: Once-daily extended release quetiapine fumarate (quetiapine XR) monotherapy was evaluated in major depressive disorder (MDD).Method: This was an 8-week (6-week randomized-phase; 2-week drug-discontinuation/tapering phase), double-blind, parallel-group, placebo-controlled study. The primary outcome measure was Montgomery-Åsberg Depression Rating Scale (MADRS) total score randomization-to-Week 6 change. Other assessments included the Hamilton Rating Scale for Depression, the Hamilton Rating Scale f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
92
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 100 publications
(103 citation statements)
references
References 37 publications
10
92
1
Order By: Relevance
“…In contrast to the current study of youth with bipolar depression, quetiapine XR has demonstrated efficacy in the acute treatment of adults with bipolar depression or MDD (Weisler et al 2009;Bauer et al 2010;Suppes et al 2010). In particular, an 8-week, placebocontrolled study of adults with bipolar depression showed significant efficacy for quetiapine XR (300 mg/day) versus placebo, measured by Montgomery-Asberg Depression Rating Scale (MADRS) score, with divergence from the first week of treatment (Suppes et al 2010).…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…In contrast to the current study of youth with bipolar depression, quetiapine XR has demonstrated efficacy in the acute treatment of adults with bipolar depression or MDD (Weisler et al 2009;Bauer et al 2010;Suppes et al 2010). In particular, an 8-week, placebocontrolled study of adults with bipolar depression showed significant efficacy for quetiapine XR (300 mg/day) versus placebo, measured by Montgomery-Asberg Depression Rating Scale (MADRS) score, with divergence from the first week of treatment (Suppes et al 2010).…”
Section: Discussioncontrasting
confidence: 62%
“…Quetiapine XR, in addition to efficacy as monotherapy in adults with schizophrenia, bipolar mania, and bipolar depression, has efficacy as monotherapy in adults with generalized anxiety disorder and as both monotherapy and adjunctive therapy in adults with major depressive disorder (MDD) (Kahn et al 2007;Weisler et al 2009;Bandelow et al 2010;Bauer et al 2010;Suppes et al 2010;Cutler et al 2011).…”
mentioning
confidence: 99%
“…By reviewing the titles and abstracts, 136 trials were excluded since they clearly did not meet the criteria. Full papers of five studies were examined [30][31][32][33]39], two studies were excluded since one was a study of maintenance treatment [30] and the other studied in geriatric patients [39], only three trials [31][32][33], therefore, were included in the review. No relevant, unpublished study meeting the inclusion criteria was identified.…”
Section: Study Selectionmentioning
confidence: 99%
“…Recently, some randomized-controlled trials of quetiapine have been conducted in patients with MDD [30][31][32][33]. Since most of these studies have small samples, a meta-analysis, which is more powerful in estimating the true effect size, may be a strategy to confirm its efficacy and safety.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, quetiapine (Calabrese 2005;Thase 2006;Suppes 2009) and olanzapine (Tohen 2003;Vieta 2010) have been successful for bipolar depression, while for major depressive disorder, quetiapine has been efficacious as a solo agent (Cutler 2009;McIntyre 2009;Weisler 2009) and as an adjunct to anti depressants (Dannlowski 2008), as has aripiprazole as an adjunct in major depressive disorder (Papakostas 2005;Patkar 2006;Rutherford 2007;Schwartz 2007;Arbaizar 2009;Berman 2009;Steffens 2011) and bipolar disorder (Kemp 2007;Sokolski 2007;Arbaizar 2009). But such assumptions might not be supportable, given the complexity of schizophrenia, including its differential and multifactorial aetiology and epiphenomena.…”
Section: Are Atypical Antipsychotics Also Antidepressants?mentioning
confidence: 99%